2006
DOI: 10.1007/s11745-006-5037-2
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic recovery of exogenous oleic acid in rats on long chain or specific structured triacylglycerol diets

Abstract: Specific structured triacylglycerols, MLM (M = medium-chain fatty acid, L = long-chain fatty acid), rapidly deliver energy and long-chain fatty acids to the body and are used for longer periods in human enteral feeding. In the present study rats were fed diets of 10 wt% MLM or LLL (L = oleic acid [18:1 n-9], M = caprylic acid [8:01) for 2 wk. Then lymph was collected 24 h following administration of a single bolus of 13C-labeled MLM or LLL. The total lymphatic recovery of exogenous 18:1 n-9 24 h after administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Generally cubs containing GMO are proposed to be suitable candidates for lymphatic absorption 54 by-passing the hepatic first-pass effect. line except T-cubs (insignificant difference from negative control) (Table 4) showing superior effect over free drug and all other studied formulations.…”
Section: Pip-loaded T-cubs As Brain-targeted Oral Nanomedicine In Admentioning
confidence: 99%
“…Generally cubs containing GMO are proposed to be suitable candidates for lymphatic absorption 54 by-passing the hepatic first-pass effect. line except T-cubs (insignificant difference from negative control) (Table 4) showing superior effect over free drug and all other studied formulations.…”
Section: Pip-loaded T-cubs As Brain-targeted Oral Nanomedicine In Admentioning
confidence: 99%
“…The medium-chain fatty acids at sn-1,3 positions could be hydrolyzed easier in the body than the long-chain fatty acids and thus could be utilized as a quick energy source (Ding et al 2009). Free medium-chain fatty acids have lower tendencies to be deposited in human adipose tissue (Nagao & Yanagita 2010, Vistisen et al 2006. Meanwhile, the remaining 2-MAGs with long-chain fatty acids still provide essential fatty acids and can be absorbed well through the intestinal wall.…”
Section: Production Of Structured Triacylglycerolsmentioning
confidence: 99%
“…Vandenberghe et al ( 8 ) reported that both caprylic (C8:0) and capric acid (C10:0) are effective in increasing plasma ketones, and may potentially provide constant energy for the body. In addition, it has been reported that MCFA also have a weak tendency to accumulate in adipose tissue ( 6 , 9 11 ).…”
Section: Introductionmentioning
confidence: 99%